Opinions of the Midwives about Enabling Factors of Skin-To-Skin Contact Immediately after Birth: A Descriptive Study. - Fatemeh Nahidi; Sedigheh Sadat Tavafian; Mohammad Haidarzade; Ebrahim Hajizadeh (Tehran University of Medical Sciences, 2014)
Objective:Despite the benefits of mother-newborn skin-to-skin contact (SSC) immediately after birth, the process has not been universally implemented as routine care for healthy term neonates. The purpose of this study was to determine opinions of the midwives about enabling factors of SSC immediately after birth in Tehran hospitals in 2012- 2013. Materials and methods:This study has been conducted in a descriptive method based on PRCEDE-PROCEED model. The samples were 292 midwives from 18 hospitals. We used stratified and then simple random sampling. In this study midwives were working at delivery room; deliveries were conducted by midwives or they were in charge of the newborn immediately after birth. Data collection instrument was a self developed questionnaire concerning the enabling factors in the SSC. We applied face and content validity ratio (CVR), content validity index (CVI) and item impact method for the instrument's validity and Cronbach's Alpha for reliability. Finally, data were analyzed and interpreted using spss-18 through descriptive statistics. Results:The results show that 90.4% of the midwives believed in necessity of a plan, 96.2% believed that good services should be provided to mothers, and 97.9%, 85.3% and 93.8% of them believed there is a need for private space, essential facilities and essential equipment for skin contact process; with Cronbach's Alpha of 0.731, 0.551, 0.501, and 0.600 respectively. Conclusion:Most of the midwives believed that enabling factors concerning the successful SSC are effective. We suggest further studies on other enabling factors effective in SSC from the view point of midwives, gynaecologists and caregivers.